Dinámica de la concentración y acumulación de nutrimentos en los componentes de la biomasa aérea de Cedrela odorata l. en costa rica - Ramírez, Daniel (2018)
Concentration dynamics and nutrient accumulation in above ground biomass components of Cedrela odorata L. in Costa Rica. Present study was conducted aiming to study nutrient concentration and accumulation dyna mics on Cedrela odorata L. (Meliaceae) trees to improve knowledge and management on tropical forestry plantations. False time series (chrono sequences) from 15 stands on Tropical Very Humid Forest of Costa Rica were used to determine aboveground biomass, nutrient concentration and to estimate nutrient accumulation on aboveground biomass components of selected trees. As a result, nutrient concentration showed a trend to decrease and followed the order nitrogen > potassium > magnesium > calcium > sulfur > phosphorus for macro nutriments, while minor elements followed the order iron > boron > zinc > manganese > cooper > aluminum. Distinguish high potassium concentration values on petioles were measured (1.46±0.48%), contrasting lower values of this nutriment on leaves (1.09±0.21%). Linear regression models were developed to evaluate behavior of nutrient concentration, and it was found a decreasing trend in nitrogen, phosphorus, potassium and magnesium concentration associated to tree age increase, been this behavior more evident on stem potassium concentration. On the other hand, regression models developed to evaluate behavior of nutrient accumulation on different aboveground biomass components presented exponential trend and statistical significance, especially on stem and total accumulation. These models allow to estimate possible nutrient outputs from the planting site during harvesting, as well as recycling of nutrient amounts into components of the biomass that remain at the planting site.